Semaphorins and their receptors in pancreatic cancer: Mechanisms and therapeutic opportunities - Liu, Dahai; Li, Jie; Qi, Fei; You, Hua (Frontiers in Oncology, 2023)
Pancreatic cancer (PC) is a malignant tumor with high malignancy that is difficult to diagnose and treat. The early diagnosis rate of PC is not high, the surgical mortality rate is high, the cure rate is meager, and related tests are expensive. Therefore, the significance of finding new markers for PC is self-evident. Semaphorins (Semas) have been shown to affect angiogenesis and lymphangiogenesis and can also directly affect the behavior of tumor cells. The expression and related action targets of its family members on PC are summarized in this review.